The Effectiveness Comparison of Salmeterol/Fluticasone Propionate and Formoterol Fumarate/Budesonide on Level of Asthma Control in Moderate Persistent Asthma - Resti, Riska; Tarigan, Amira Permatasari; Pradana, Andika; Wahyuni, Arlinda Sari (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2026)
Background: Asthma is a prevalent chronic respiratory disease, affecting approximately 1–18% of the population worldwide. Despite its high prevalence, a substantial proportion of patients have partially controlled asthma, and limited data on the level of asthma control remain a significant concern. This study aimed to compare the effectiveness of salmeterol/fluticasone propionate and formoterol fumarate/budesonide in achieving asthma control levels according to the ACQ-GINA criteria. Methods: A retrospective cohort study was conducted using 61 medical records from January 2017 to December 2019. Patients with moderate persistent asthma received either salmeterol/fluticasone propionate or formoterol fumarate/budesonide for at least three months. Statistical analysis was performed using Fisher’s exact test. Results: A total of 61 patients were included. Most patients had partially controlled asthma (70.5%), followed by well-controlled (19.7%) and uncontrolled asthma (9.8%). No statistically significant difference in asthma control was observed between the two treatment groups (P=0.057). Conclusion: Within the limitations of this retrospective cohort study, no statistically significant difference in asthma control was observed between salmeterol/fluticasone propionate and formoterol fumarate/budesonide.